Konstruksi Pesan Politik di Televisi Komersial Menjelang Pemilihan Umum 2014: Studi Kasus Iklan Partai Hanura, Pan, dan Gerindra - Yunus, Ulani (Humaniora, 2014)
Effective adverstisement must contain ideal message that will attract, arouse curiosity, and stimulate the action in accordance with the purpose of the advertiser. The problem identification of this study is how the political message in the TVC construction towards the 2014 election. This study aims to know how the message construction of Hanura, PAN, and Gerindra on TVC ads by the 2014 election and to know the similarities message of Hanura, PAN, and Gerindra ads as the largest ad spender in the TVC. The methodology used is qualitative analysis by Stuart Hall’s reception constructive theory. The results of this study point out that the construction of political message through the TVC from January to March 2014 was in the opposition position. The recipient constructed ideas contrary to the purpose of the advertisers. Thus, marketing communications conducted by the team of political parties in this study did not conform to expectations. While, those three political parties analyzed were carrying the same message that they sided with the poor people and promised to give hope to live well. Conclusions obtained from the results of the research are the construction of the message contains the element of appeals and emotionals instead of the element of arguments and convictions. Then the similirarity of the TVC message is the parties give a promise of hope and well living to the people yet no one conveys the answers to the concerns of the people existed since the reform era, that is about disintegration and unity in the community.